Study the absorption of diode pumped solid state laser on Ti: sapphire crystal - Bidin, Noriah; Wan Razali, Wan Aizuddin; Saidin, Mohamad Khairi (Faculty of Science, University Teknologi Malaysia, 2007)
Exciting laser material is a challenging task. Only certain source is appropriate to pump the electron to an excited state. This depends on how much the pumped source will absorb and cause the fluorescence. Hence, this research was carried out to estimate the percentage of energy absorbed in the laser material. In this case, ti:sapphire crystal was employed as an active medium. High power diode laser was used as a pumping source. A powermeter was utilized to measure the output of the beam. The absorbance power was estimated to be 1.29 w from the result of transmission and reflection measurement.